Tenun Fashion Hub: Pusat Inovasi Mode Berbasis Circular System di Jakarta Selatan dengan Pendekatan Arsitektur Ekspresionisme - Anissa Fajriani; Fisa Savanti; Dimas Wicaksono (Universitas Negeri Semarang, 2025)
Fashion serves as a medium of self-expression and identity (Kadek & Diantari, 2021), yet rapid industrialization has accelerated fast fashion cycles that generate 2.3 million tons of textile waste annually in Indonesia 12% of total household waste (waste4change, 2023). As Jakarta's fashion epicenter, South Jakarta hosts prestigious events like Jakarta Fashion Week and houses traditional weaving industries (Soe Jakarta, CTI), but lacks dedicated infrastructure for sustainable innovation. Responding to this gap, the Tenun Fashion Hub integrates circular economy principles extending product lifecycles through recycling and repair with revitalization of traditional weaving as a slow fashion alternative (Ummah, 2019; SMB Museum, 2019). The project adopts expressionist architecture to translate weaving motifs into kinetic facades and organic forms, symbolizing cultural sustainability while creating an iconic landmark in this dynamic district. Functioning as a hybrid space, it combines: (1) a production center for upcycled textiles; (2) collaborative studios for designers and artisans to preserve Indonesia’s weaving heritage (Tengku Ryo Rizqan, 2019); and (3) educational workshops promoting eco-friendly techniques. By merging closed-loop systems with cultural narratives, the hub establishes a prototype for sustainable urban fashion districts that combat environmental damage while empowering local craftsmanship.